2013
DOI: 10.1111/ijfs.12290
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hot‐air treatment, superatmospheric O2 and elevated CO2 on bioactive compounds and storage properties of fresh‐cut pomegranate arils

Abstract: Summary The impact of heat treatment using hot air (HT 45 °C and 55 °C for 1 h) and two active modified atmosphere packaging (MAP) conditions of high oxygen atmosphere (HOA: 80 kPa O2, 20 kPa N2) and high CO2 atmosphere (HCA: 20 kPa CO2, 80 kPa N2), individually or combined, on the antioxidant capacity, polyphenols, vitamin C content, total anthocyanins, polyphenoloxydase (PPO) activity and shelf life of fresh‐cut (FC) pomegranate arils stored for 14 days at 4 °C was studied. The results indicate that HT 45 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…; Maghoumi et al . ). In strawberries high oxygen atmospheres have been suggested as an effective method to inhibit fungal growth and to reduce decay incidence (Wszelaki and Mitcham ; Zheng et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Maghoumi et al . ). In strawberries high oxygen atmospheres have been suggested as an effective method to inhibit fungal growth and to reduce decay incidence (Wszelaki and Mitcham ; Zheng et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Maghoumi et al . ). The effectiveness of oxygen treatments varies with species and developmental stages (Kader and Ben‐Yoshua, ).…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, postharvest thermal treatments (TT), applied either by immersion into a hot water bath or by elevating the air temperature in storage rooms during certain periods of time, have been reported to exert both positive effects on insect quarantine treatments as well as a decrease in the incidence of many postharvest diseases. They can also delay the changes associated with the process of ripening as well as the incidence of certain physiological disorders, such as CI (Fallik, ; González‐Aguilar et al, ; Lamikanra & Watson, ; Lurie & Sabehat, ; Maghoumi et al, ; Saltveit, ). Studies conducted on such products as the cucumber, the tomato, and the apple have demonstrated that TT induces tolerance to CI by reducing the sensitivity of tissues to this physiological disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, packaging under either an N 2 or a 5% O 2 + 4% CO 2 atmosphere has successfully been used to main- Similarly, postharvest thermal treatments (TT), applied either by immersion into a hot water bath or by elevating the air temperature in storage rooms during certain periods of time, have been reported to exert both positive effects on insect quarantine treatments as well as a decrease in the incidence of many postharvest diseases. They can also delay the changes associated with the process of ripening as well as the incidence of certain physiological disorders, such as CI (Fallik, 2004;González-Aguilar et al, 2000;Lamikanra & Watson, 2007;Lurie & Sabehat, 1997;Maghoumi et al, 2013;Saltveit, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The modified atmosphere can be passive or active, depending on the package that is sealed under normal air conditions or with a gas mixture. Many researchers have demonstrated that MAP is able to extend the shelf life of fresh as well as fresh-cut fruit and vegetables for many foods (Jacxsens et al, 2001;Brecht et al, 2003;Saltveit, 2003;Rojas-Gra€ u et al, 2009;Cefola et al, 2014;Maghoumi et al, 2014). However, Waghmare & Annapure (2015) reported that MAP (5% O 2 , 10% CO 2 , 85% N 2 ) alone was not effective in preserving the quality of fresh-cut coriander and preventing microbial growth as well.…”
Section: Introductionmentioning
confidence: 99%